Perceived occupational balance in people with stroke. Issue 4 (13th February 2021) - Kassberg, Ann-Charlotte; Nyman, Anneli; Larsson Lund, Maria
Abstract: Background: The balance of activities in daily life can become disrupted after a stroke; however, previous research has mainly focused on the performance of daily activities. Therefore, it is important to understand the impact that stroke has on various aspects of balance in activities for working-age people. Purpose: To describe how persons with stroke perceived their occupational balance and to explore whether occupational balance was associated with the severity of disability, fatigue and sociodemographic characteristics. Methods: This cross-sectional study included 63 working-age persons with stroke. The Occupational Balance Questionnaire, Glasgow Outcome Scale and Fatigue Severity Scale were used and analyzed statistically. Results: The majority of participants disagreed or strongly disagreed that they perceived occupational balance in most of the investigated aspects. Moreover, few significant associations were found between total summed occupational balance and injury and sociodemographic characteristics. Conclusion: These results demonstrate the importance of considering occupational balance in the rehabilitation of persons with stroke to support their engagement in a variety of meaningful activities that contribute to health. IMPLICATIONS FOR REHABILITATION: Rehabilitation need to support persons with stroke to monitor their entire patterns of activities and perceived balance to support wider engagement in meaningful activities and promote health. Balance between all kinds of activities in daily life besides work, needs to be considered in the later phase of rehabilitation in persons with stroke. A majority of the participants with stroke in this study disagreed that they had a satisfying level of occupational balance. Perceived balance between all activities in daily life can together with performance of activities add to the understanding of consequences after stroke.